Selge, Türkei: Eine Stadt in den pisidischen Bergen - Nollé, Johannes (e-Forschungsberichte des DAI, 2023)
Between 1987 and 2013 the research work at Selge was carried out by J. Nollé, focusing on surveys and epigraphic and numismatic evidence. A corpus of the inscriptions of Selge was already published in 1991, the corpus of the coins, minted by Selge during the first three centuries of the Roman Empire, will be completed in 2014. New evidence and intensive research work have generated new knowledge about the history and the economical situation of this important Pisidian city. The depiction of Selge’s remarkable main sanctuary on the city coins raised the question how two tree trunk-like objects in the centre of this cult place are to be explained. By a happy coincidence the trunks could be identified as giant juniper rsp. cypress tree-trunks. This identification allows us to draw conclusions regarding Selge’s role as an important timber producer.